The use of the activity-centered teaching approach for pupil referrals in the Division of City School, Pasay City - Mercado, Leticia I. (College of Education, University of the Philippines Diliman, 1975)
The purpose of the study is to suggest the use of activity as a core approach using the integrative method in the teaching of pupil referrals for special classes in the Division of City Schools, Pasay City. Included in the study are illustrative samples of activity units, showing how an activity may stimulate the child to enter into other experiences which are purposeful and have legal connections with the unit of study. Activities chosen lay stress on their therapeutic, psychomotor, and cognitive values to pupil referrals.